JIVA: Burnout Early Detection and Mindfulness Therapy for College Students to Prevent Self-diagnosis in the Quarter Life Crisis Era - Wibawa, Made Suda Cakra; Wibawa, I Gede Artha; Suryandari, Ni Komang Ayu Diah; Wiryantara, I Putu Krisna; Sucipta, I Gede Wahyu Parama (Media Informatika, 2024)
Burnout has harmed students. Recent ventures, such as counseling, have yet to provide significant benefits. Furthermore, there is a tendency for college students to self-diagnose. However, self-diagnosis often leads to misdiagnosis and mishandling, triggering more severe health problems. This study aims to know if Jiva can be used as burnout early detection and mindfulness therapy for college students to prevent self-diagnosis in the quarter-life crisis era. The research was conducted at Marcopolo Bali International from October-December 2022. Population of this study was eight respondents for the small group trial and 80 respondents for the large group trial. The research method used is Research & Development with ADDIE research design. Qualitative and quantitative data will be analyzed descriptively. Jiva app is software that integrates Burnout Early Detection and Body Scan Meditation. The creation of the application will help find burnout as early as possible and treat student burnout. The results of the material validation test showed that the application was included to excellent category with the score of 4.75 (95%). The results of the media validation test showed that the application was included to excellent category with the score of 4.32 (86%). Furthermore, the small group trial pointed to the application belonging to good category with the score of 3.95 (79%). The large group trial pointed to good category with the score of 3.9 (78%). Thus, Jiva can be used as burnout early detection and mindfulness therapy for college students to prevent self-diagnosis in the quarter-life crisis era.